Physico-chemical assessment of water resources in Pulau Pangkor, Perak, Peninsular Malaysia - Yusoff, Mohd Kamil; Mohamed @ Mohd Ramli, Khairul Nizam; Ismail, Mohd Zamani; Johan, Shamsuddin; Mohd Hisyam, Nor Hanisah (Forestry Department Peninsular Malaysia, 2019)
The main aim of this investigation was to assess the water resource in Pulau Pangkor in terms of physico-chemical characteristics. The river flow represents the physical characteristics while the chemical characteristics represent by selected water quality parameters namely temperature, pH, electrical conductivity, salinity, total dissolved solids, dissolved oxygen, turbidity, total suspended solids, biochemical oxygen demand, ammoniacal-nitrogen and chemical oxygen demand. The study was carried out during the scientific expedition from 15th -21st July 2017. Based on accessibility, ten sampling locations were selected for the purpose of water resource assessment. At each sampling station, the river water velocity, depth of water, river cross-sectional area were measured and later the data were used to estimate the river discharge. The river water quality status were assessed using Harkin’s Index. The results showed that the river water velocity ranges from 0.1 to 0.6 m/second with an estimated discharge ranges from 121 to 1244 m3/day. Based on Harkin’s Index, the water quality index ranges from 0.016 (Class I) to 0.216 (Class II) where eight sampling locations fall under Class I and the remainder fall under Class II. In conclusion the water bodies from all sampling locations are of high quality status.